2010
DOI: 10.1007/s10529-010-0469-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shear on proteins in solution

Abstract: The effects of "shear" on proteins in solution are described and discussed. Research on this topic covers many decades, beginning with investigations of possible denaturation of enzymes during processing, whilst more recent concerns are how the quality of therapeutic proteins might be affected by shear or shear related effects.The paradigm that emerges from most studies is that shear in the fluid mechanical sense is unlikely by itself to damage most proteins and that interfacial phenomena are critically import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
123
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(127 citation statements)
references
References 86 publications
(84 reference statements)
1
123
0
Order By: Relevance
“…As mentioned above, the result may be that the protein experiences a wide range of pH, ionic strength, protein concentrations, and contact materials during the process. In addition to that, it has to be considered that at large scale the protein is exposed to mechanical stresses such as agitation in tanks and pumping (Thomas and Geer, 2011). Once the protein has been purified, it is typically filled into bottles, bags, or cryo-vessels for further freezing and storage.…”
Section: Aggregation During Purificationmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned above, the result may be that the protein experiences a wide range of pH, ionic strength, protein concentrations, and contact materials during the process. In addition to that, it has to be considered that at large scale the protein is exposed to mechanical stresses such as agitation in tanks and pumping (Thomas and Geer, 2011). Once the protein has been purified, it is typically filled into bottles, bags, or cryo-vessels for further freezing and storage.…”
Section: Aggregation During Purificationmentioning
confidence: 99%
“…During agitation of protein solutions a gas/ liquid interface is created at which aggregation predominantly occurs. There have now been many studies specifically investigating how proteins behave at gas-liquid interfaces (Thomas and Geer, 2011). Mahler et al (2005) claimed that agitation in the presence of a (hydrophobic) gas-liquid interface caused aggregation of immunoglobulin-G1 (IgG1).…”
Section: Agitationmentioning
confidence: 99%
See 1 more Smart Citation
“…The force applied onto a protein as a consequence of hydrodynamic flow has also been observed to trigger protein aggregation and has fundamental (3), medical (4), and industrial relevance, especially in the manufacture of biopharmaceuticals (5)(6)(7)(8). Although a wealth of studies have been performed (7,(9)(10)(11)(12)(13), no consensus has emerged on the ability of hydrodynamic flow to induce protein aggregation (7,14,15). This is due to the wide variety of proteins used (ranging from lysozyme, BSA, and alcohol dehydrogenase to IgGs), differences in the type of flow field generated (e.g., shear, extensional, or mixtures of these), and to the presence or absence of an interface (16).…”
mentioning
confidence: 99%
“…The low decrease in absorbance for the permeate indicated that phospholipase A 2 did not show the ability to catalyze the hydrolysis of phospholipids. This might be explained due to the denaturation of the enzyme during permeation tests through the membrane, possibly as the result of the interfacial interaction of the macromolecule with the solid irregular pores (Thomas and Geer, 2011). This result is significant, since the permeate can improve product safety.…”
Section: Phospholipase Activitymentioning
confidence: 99%